2016
DOI: 10.1177/1367006914566831
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the social meaning of contemporary urban vernaculars: Perceptions and attitudes about Citétaal in Flanders

Abstract: This paper aims to provide a more nuanced understanding of the social meaning of a contemporary urban vernacular called Citétaal (Citélanguage). While most studies on the perception of urban vernaculars have applied qualitative discursive methods, we investigate the perception of and attitudes towards Citétaal by combining a qualitative and quantitative approach. In a discursive analysis of online surveys and social media networks, we analyze how this variety is perceived and represented on a collective level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…The fact that participants refer to standard Swedish (as opposed to slang use, anglicisms, youth language, for example) as an abstract referee when discussing their own language use also tells us that the awareness of referees does not only involve the differences in language proficiency, but indeed also social differences (cf. Madsen and Svendsen 2015;Marzo 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that participants refer to standard Swedish (as opposed to slang use, anglicisms, youth language, for example) as an abstract referee when discussing their own language use also tells us that the awareness of referees does not only involve the differences in language proficiency, but indeed also social differences (cf. Madsen and Svendsen 2015;Marzo 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In a number of studies, participants express attitudes towards language by using value terms, and positioning themselves in relation to other speakers, making their ideologies concerning language (standard and non-standard) very visible. In their Copenhagen interviews, Madsen and Svendsen (2015) found that adolescents label ways of speaking which they do not themselves report using as 'integrated ', 'sophisticated', 'academic', 'privileged', etc. At the other end of the spectrum, Marzo (2016) found that, while Citétaal, an urban Flemish vernacular used in former ghettoised areas, is generally stigmatised and associated with negative values, it is nevertheless associated with positive values carrying prestige, such as speaker attractiveness, coolness and humour. Trudgill (1972, 184) found that, in Norwich, male speakers associate working class, non-standard speech with covert positive values and prestige.…”
Section: Attitudes Standard Language Ideology and The Case Of Swedenmentioning
confidence: 99%
“…Madsen & Svendsen (2015) find that adolescents in diverse urban neighbourhoods in Norway and Denmark sometimes distance their own speech from that of 'integrated', 'sophisticated', or 'privileged' speakers. Marzo (2016) investigates the covert prestige of an urban vernacular of Flemish and finds that listeners consider Citétaal as a variety used by foreign speakers of Dutch, and that even within the speech community, not all listeners equate social values expressed through speech with speaker attractiveness. Positive social values can thus be attached to varieties of speech which from the outside (or even within the group of speakers) are stigmatised.…”
Section: Language Ideology Attitudes and Identitiesmentioning
confidence: 99%
“…Although not all youngster consistently make use of Citélanguage, it has become distinctive and recognizable to many. However, it also yields (stereotypical) associations based on personal and mass mediated experiences (Marzo 2015;Svendsen and Marzo 2015). So far, it remains unclear to what extent the use of this variety in advertisements emphasizes (or reduces) social distance between the speaker and the reader and how advertisers may benefit from a perceived similar social identity.…”
Section: Language Accommodation In a Multicultural Advertising Enviromentioning
confidence: 99%
“…Consumer responses are contrasted to responses to similar slogans in standard Dutch with a specific focus on the social meanings attributed to Citélanguage. As this urban vernacular has been previously found to elicit both positive and negative language attributions, which stem from the local origins of the language variety (the city of Genk) as well as from the stereotypes that exist about its speakers for their migration backgrounds (Marzo 2015;Koeman et al 2016), we particularly scrutinize the social meanings attributed to Citélanguage. We will question which consumers respond favorably to Citélanguage and how this affects their responses towards advertisements that try to accommodate urban youth?…”
Section: Introductionmentioning
confidence: 99%